Edgar Allan Poe and neurology - Hélio Afonso Ghizoni Teive; Luciano de Paola; Renato Puppi Munhoz (Arquivos de Neuro-Psiquiatria)
Edgar Allan Poe was one of the most celebrated writers of all time. He published several masterpieces, some of which include references to neurological diseases. Poe suffered from recurrent depression, suggesting a bipolar disorder, as well as alcohol and drug abuse, which in fact led to his death from complications related to alcoholism. Various hypotheses were put forward, including Wernicke's encephalopathy.